The research of the scattered radiation of electrons linear accelerator - I. M. Vyshnevskyi; T. V. Khrin; V. I. Sakhno; O. V. Sakhno; A. G. Zelinskyy; S. P. Tomchay; N. V. Khalova (Âderna Fìzika ta Energetika, 2018)
The results of experimental measurement of undesirable radiation leakage from linear accelerator (electrons energy 4 MeV) of “Electronica” series are discussed. The scheme of measuring means and methods of processing of the information are updated. Radiated background from installation was investigated.